Concrete mix with wastepaper - Mohamad Shukeri, Ritzawaty; Abdul Ghani, A. Naser (2008)
Malaysia is facing a serious challenge in disposing of waste in the many landfills throughout the country that are near or at capacity. The landfill situation is resulting in high disposal costs and potential environmental problems. If current trends continue, with waste production projected to grow by 5% each year, landfills would be at full capacity by 2020. This paper reports on the results of an investigation of utilization of wastepaper as additional materials in concrete mixes to be used for housing projects, for which it must be assured that the resulting concrete has the proper mechanical strength. Concrete mixes containing various contents of the paper were prepared and basic strength characteristics such as compressive strength, splitting tensile, flexural, and water absorption were determined and compared with a control mix. Four concrete mixes containing of the waste, which are control mix, 5%, 10%, 15% as an additional materials to concrete were prepared with ratios of 1:2:3 by weight of cement, sand, and aggregate respectively. The maximum size of aggregate was 20mm. In earlier work on the subject during trial mix, it was shown that the addition of wastepaper reduces the mechanical strength of concrete. The test results also revealed that as the content of the paper increased the water to cement ratio for the mix was also increased. With the addition of 25% wastepaper in proportion to the amount of cement, the mechanical strength decreases significantly. Overall, a high correlation was observed between density and strength of concrete containing paper.